First case of Aspergillus caelatus airway colonization in a Chronic Obstructive Pulmonary Disease patient. (April 2019) - Le Pape, Patrice; Ximenes, Rafael Matos; Ariza, Beatriz; Iriarte, Juan; Alvarado, Jaime; Robert, Estelle; Sierra, Claudia; Montañez, Anita; Álvarez-Moreno, Carlos
Abstract: Background: During a cross-sectional study on allergic aspergillosis in Chronic Obstructive Pulmonary Disease patients in Bogotá, Colombia, we reported the case of a 65-year-female patient with GOLD 2011 D classification, presenting dyspnea at the time of visit and aspergillus in repeated sputum cultures. Methods: The isolate was identified at the section level based on macroscopic and microscopic characteristics and gene sequencing was used for precise molecular identification. Antifungal sensibility was determined by Sensititre YeastOne™ while virulence was assessed using a Galleria mellonella larvae model. Results: The clinical isolate was first identified as Aspergillus section Flavi and sequencing of β-tubulin and calmodulin genes, in addition to the identification of alfR (aflatoxin regulator) gene, allowed the undoubted identification of the clinical isolate as Aspergillus caelatus . It exhibited virulence in G. mellonella similar to A. flavus and a high in vitro susceptibility against all antifungals except for amphotericin B. Conclusion: This is the first human case of airway colonization attributed to A. caelatus . Resistance pattern justified the interest to discriminate this cryptic species.